Pengaruh Kualitas Produk Dan Harga Terhadap Kepuasan Konsumen ( Studi Kasus Pada Cam Cafe Brebes ) - Ahmad Dani Riyanto; Roby Setiadi; Andi Yulianto (Jurnal Manajemen Riset Inovasi, 2023)
One of the problems faced by cafes is how to keep consumers satisfied and increase their level of loyalty. This research aims to determine the effect of product quality and price on consumer satisfaction, the type of research used is quantitative. The population in this study was 480 cam cafe consumers. The sampling technique used the Solvin formula with a margin of error of 5% and obtained 218 respondents. The types of data used are secondary data and primary data. The data can be carried out using validity and reliability tests, followed by classical assumption tests and multiple linear regression tests. Hypothesis testing is carried out using the t test, f test and coefficient of determination. The results of this research state that the product quality and price variables have a significant and positive effect on consumer satisfaction. This can be seen from the results of the t test on the product quality variable, namely t count 4,470 > 1,971 t table with a significance value of 0.00 < 0, 05 and the price variable also has a significant and positive effect on consumer satisfaction, namely getting a calculated t value of 7,263 > 1,971 t table value with a significance value of 0.00 < 0.05. The f test obtained a calculated f value of 44,553 and an f table value of 3.04 so that 44,553 > 3.04 concluded that product quality and price jointly influence consumer satisfaction. The magnitude of the influence of product quality and price on consumer satisfaction is 55%